1992
DOI: 10.1016/0014-5793(92)81354-o
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic acetylcholine receptor produced in recombinant baculovirus infected Sf9 insect cells couples with endogenous G‐proteins to activate ion channels

Abstract: Following the inl'ection of insect ovarian cells ($)9) with recombinant baculoviras bearing the eDNA coding for the rat muscarini¢ acetyleholine (ACh) receptor subtype m3, ionic flax across the membrane in response to the application of ACh was ¢xamin~ elcctrophysiologically. We show that ACh activates potassium currents. The respons~ is abolish~ when cells arc treated with pertussis toxin. No ACh-induced currents are observed from uninfected cells or cells infected with virus which do not contain the eDNA cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Indirect evidence for such a GTP-binding protein has been reported (Mumby et al, 1986;Graber et al, 1992), but up to now a detailed analysis has never been made. Although the immunoblotting experiments suggest that G,,o subunits are absent in insect cells, there has been a recent report that rat muscarinic M, receptors, produced in Sf9 cells, can couple with endogenous pertussis-toxin-sensitive GTP-binding proteins to modulate calcium-activated K' channels (Vasudevan et al, 1992). It is interesting that the fi subunit of the endogenous insect GTP-binding protein differs in apparent molecu-lar mass from mammalian and avian p subunits, although it cross-reacts with the antibody which is directed against the C-terminus of the subunit.…”
Section: Western-blot Analysis Of Endogenous Gtp-binding Proteins Fromentioning
confidence: 99%
“…Indirect evidence for such a GTP-binding protein has been reported (Mumby et al, 1986;Graber et al, 1992), but up to now a detailed analysis has never been made. Although the immunoblotting experiments suggest that G,,o subunits are absent in insect cells, there has been a recent report that rat muscarinic M, receptors, produced in Sf9 cells, can couple with endogenous pertussis-toxin-sensitive GTP-binding proteins to modulate calcium-activated K' channels (Vasudevan et al, 1992). It is interesting that the fi subunit of the endogenous insect GTP-binding protein differs in apparent molecu-lar mass from mammalian and avian p subunits, although it cross-reacts with the antibody which is directed against the C-terminus of the subunit.…”
Section: Western-blot Analysis Of Endogenous Gtp-binding Proteins Fromentioning
confidence: 99%
“…Still, functional coupling to endogenous G proteins was depicted for receptors known to be coupled to pertussissensitive G proteins such as human serotonin 5HT 1A (46) and 5HT 1B (45). Similarly, Vasudevan et al (49) reported that the rat muscarinic acetylcholine receptor subtype m 3 activates potassium channels, and Oker-Blom et al found (50) that the human ␣ 2 C-C4 adrenergic receptor inhibits forskolin-stimulated adenylyl cyclase in Sf9 cells. These observations suggest that receptors coupled to G o and/or G i may interact with Sf9 endogenous G␣ subunits.…”
Section: Effect Of the Amino-terminal Histidine Tag On Receptor Exprementioning
confidence: 99%
“…Recently, several groups have reported the purification of G-protein-coupled receptors from insect cells infected by a recombinant baculovirus (George et al, 1989;Parker et al, 1991 ;Reilander et al, 1991 ;Vasudevan et al, 1991). They also showed that the purified receptors were able to couple with Gproteins in reconstituted systems (Parker et al, 1991 ;Reilander et al, 1991) as well as in in vivo (Kleyman et al, 1993;Vasudevan et al, 1992).…”
mentioning
confidence: 99%